Keputusan Pembelian Produk di Shopee Terhadap Mahasiswa Manajemen Angkatan 2020 Universitas Buana Perjuangan Karawang - Dini Oktaviani; Dedi Mulyadi (Yayasan Daarul Huda Kruengmane, 2023)
The research objective is to find out how people can easily use the Shopee application to make a purchase decision. The method used in this study was to send a questionnaire to students at the University of Buana Perjuangan Karawang Management 2020 with 100 respondents who had shopped on the Shopee platform. The results of the study show that there is an increase in online shopping by male consumers at Buana Perjuangan University, Karawang Management 2020 and from an age group. With a comparison of prices and product quality between online shop platforms, it can affect purchasing decisions by consumers. This is influenced by the many online shops that sell goods by live streaming which can attract the attention of consumers where it can be a product purchase decision. With so many consumers making product purchase decisions at Shopee due to the very easy use of the Shopee platform, making transactions easily, and the many options for payment such as COD, as well as through partners/agents and others, this makes the Shopee platform an advantage.